Influence of varietal qualities of winter annual wheat on dynamics of sowing campaigs and processing behaviour of grain in storage. - Н. О. Ящук (Plant Varieties Studying and Protection)
Dynamics of technological and sowing indexes of grain of wheat winter-annual kinds of Natsionalna, Stolichna, Artemis in the course of long-term storage is studied. It is positioned that the best sowing indexes throughout all shelf-life the kind of Stolichna, and technological had a kind of Natsionalna. The optimum shelf-life of grain of investigated kinds has compounded six months.